Pheromone induction of agglutination in Saccharomyces cerevisiae a cells. - Terrance, K (1987)
a-Agglutinin, the cell surface sexual agglutinin of yeast a cells, was assayed by its ability to bind its complementary agglutinin, alpha-agglutinin. The specific binding of 125I-alpha-agglutinin to a cells treated with the sex pheromone alpha-factor was 2 to 2.5 times that of binding to a cells not treated with alpha-factor. Competition with unlabeled alpha-agglutinin revealed that the increased binding was due to increased cell surface expression of a-agglutinin, with no apparent change in the binding constant. The increase in site number was similar to the increase in cellular agglutinability. Increased expression of a-agglutinin followed the same kinetics as the increase in cellular agglutinability, with a 10-min lag followed by a 15- to 20-min response time. Induction kinetics were similar in cells in phases G1 and G2 of the cell cycle. Maximal expression levels were similar in cells treated with excess pheromone and in cells exposed to pheromone after destruction of constitutively expressed a-agglutinin.